Fatty acids and fat-soluble vitamins in ewe's milk predicted by near infrared reflectance spectroscopy. Determination of seasonality. (1st January 2017) - Revilla, I.; Escuredo, O.; González-Martín, M.I.; Palacios, C.
Highlights: NIRS analysis reliable predicted ewe' milk fatty acid profile. NIRS analysis allowed an acceptable prediction of retinol and α-tocopherol. Season of milk production can be identified using only the NIR spectra. Abstract: The aim of the present work was to determine the fatty acid and fat-soluble vitamin composition and the season of ewe's milk production using NIR spectroscopy. 219 ewe's milk samples from different breeds and feeding regimes were taken each month over one year. Fatty acids were analyzed by gas chromatography, and retinol and α-, and γ-tocopherol by liquid chromatography. The results showed that the quantification was more accurate for the milk dried on paper, except for vitamins. Calibration statistical descriptors on milk dried on paper were good for capric, lauric, myristic, palmitoleic, stearic and oleic acids, and acceptable for caprilic, undecanoic, 9c, 11tCLA, ΣCLA, PUFA, ω3, ω6, retinol and α-tocopherol. The equations for the discrimination of seasonality was obtained using the partial least squares discriminant analysis (PLSDA) algorithm. 93% of winter samples and 89% of summer samples were correctly classified using the NIR spectra of milk dried on paper.